Qu'est-ce qu'un texte numérique?--A new rationale for the digital representation of text. - van Zundert, Joris J.; Andrews, Tara L. (Digital Scholarship in the Humanities)
In this article we aim to provide a minimally sufficient theoretical framework to argue that it is time for a re-conception of the notion of text in the field of digital textual scholarship. This should allow us to reconsider the ontological status of digital text, and that will ground future work discussing the specific analytical affordances offered by digital texts understood as digital texts. Following from the argument of Suzanne Briet regarding documentation, referring to Eco's understanding of 'infinite semiosis', and accounting for the reciprocal effects between carrier technology and meaning observed by McLuhan, we argue that the functions of document and text are realized primarily by their fluid nature and by the dynamic character of their interpretation. To define the purpose of textual scholarship as a 'stabilisation' of text is therefore fallacious. The delusive focus on 'stability' and discrete 'philological fact' gives rise to a widespread belief in textual scholarship that digital texts can be treated simply as representations of print or manuscript texts. On the contrary--digital texts are texts in and of themselves in numerous digital models and data structures which may include, but is not limited to, text meant for graphical display on a screen. We conclude with the observation that philological treatment of these texts demands an adequate digital and/or computational literacy.